PENGARUH NON-LINEAR KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN YANG DIUKUR DENGAN TOBIN'S Q - Makaryanawati Makaryanawati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2003)
The principle aim of a firm is to improve the wealth of the shareholders through the increase of the firm value. Further, the improvement of the shareholders ' wealth is led to increase of the stock price.The conflict of interest between the management and the shareholders is based on the agency theory. One of the motif is the separation between control and ownership functions which causes the management cannot feel the effects of error in business decision making directly. The increase of managerial ownership can be employed to cover up this problem.This research develop one hypotheses. This hypotheses is managerial ownership has a non-linear effect to the firm value. Population of the research are non financial firms registered in the Jakarta Stock Exchange in the year 1994-2000.The research provides empirical evidence that managerial ownership shows a non-linear relation to the firm value, but is insignificant statistically. Meanwhile the control variables of profitability, leverage and size are positive and significant determinant offirm value.